Resilience outcomes and associated factors among workers in community-based HIV care centres during the Covid-19 pandemic: A multi-country analysis from the EPIC program - Marion Di Ciaccio; Nicolas Lorente; Virginie Villes; Axel Akpaka Maxence; Claudia Marcela Vargas Pelaez; José Rafael Guillen; Ingrid Castillo; Cinta Folch; Rokhaya Diagne; Lucas Riegel; Rosemary M. Delabre; Daniela Rojas Castro (Elsevier, 2023)
Introduction: Community health workers (CHW) were integral in the COVID-19 response, particularly concerning services for populations vulnerable to HIV. Little is known regarding the mental health of CHW during the COVID-19 crisis. The objective of this study was to study resilience of CHW working in HIV non-governmental organizations. Methods: An anonymous online, cross-sectional questionnaire was implemented during 2021 among CHW in Benin, Colombia, Guatemala, and Spain. Three scales were used to assess mental health: the 6-item Brief-Resilience Scale, the 9-item Patient Scale Questionnaire and the 7‐item Generalized-Anxiety-Disorder scale. Logistic regression models were used to identify factors associated with "low" resilience vs "normal" or "high" resilience. Results: Among 295 respondents, the median standardized resilience score was 58.33 (IQR = [50.0-75.0], n = 267), 18.52 (IQR = [7.4-33.3], n = 282) for standardized depression score and 19.05 (IQR = [4.8-33.3], n = 274) for standardized anxiety score. Standardized resilience score was negatively correlated with standardized anxiety score (rho = -0.49, p < 0.001, n = 266) and standardized depression score (rho = -0.44, p < 0.001, n = 267). Conclusions: Normal or high level of resiliency in the HIV CHW were observed during the COVID-19 crisis. Self-efficacy, through COVID-19 prevention training, was a factor associated with resilience. Health policy must place CHW at the core of the healthcare system response to Covid‐19 and to future health emergencies, as they ensure continuity of care for many diseases including HIV among vulnerable populations.